2014
DOI: 10.1111/ics.12143
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of phenolic compounds from Phyllanthus emblica L. and evaluation of antioxidant activities

Abstract: The result of this study showed that UAE was a suitable method for the extraction of total phenolic compounds. Moreover, the author's main finding in this work is the fact that phenolic compounds from P. emblica show excellent antioxidant activity in multi-test systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
1
6
0
3
Order By: Relevance
“…The chelating capacity of honey is slightly higher than that of cane sugar in the controls (Unpublished data). Present results supported the previous report by Tsai et al (2014), with respect to the chelating property of P. emblica. Fermented P. emblica fruit juices are strong enough to stabilize the oxidized form of the metal ion.…”
Section: Antioxidant Properties and Other Evaluation Of The Productsupporting
confidence: 93%
See 2 more Smart Citations
“…The chelating capacity of honey is slightly higher than that of cane sugar in the controls (Unpublished data). Present results supported the previous report by Tsai et al (2014), with respect to the chelating property of P. emblica. Fermented P. emblica fruit juices are strong enough to stabilize the oxidized form of the metal ion.…”
Section: Antioxidant Properties and Other Evaluation Of The Productsupporting
confidence: 93%
“…A recent study has reported the phenolic components extraction from P. emblica by comparing conventional and ultrasound-assisted extractions techniques (Tsai et al, 2014). Sripanidkulchai & Junlatat (2014) also reported the antioxidant properties, and anti-inflammatory effect of phenolic content in P. emblica branch ethanolic extract by maceration and methanolic extract by Soxhlet apparatus.…”
Section: Polyphenol Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was carried out in the center of plant breeding and propagation, Departamento de Fitotecnia ( canopy, mixed, and dried in an oven with forced-air circulation at 65°C, until reaching constant mass; the leaves were then ground in a micro mill MA-630 (Marconi, Piracicaba, SP, Brazil) until reaching the granulometry of commercial thick-grind mate, and used for separation of samples. Total phenolics and flavonoids were extracted according to Tsai et al (2014). The extraction conditions were optimized with type and composition of solvents and time of extraction in ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal extraction conditions were found to be at ultrasonic temperature of 30°C, ultrasonic time of 5 min, ultrasonic power of 150 W, sample to solvent ratio of 8:100 g mL -1 and acetone concentration of 60%. Under these optimal conditions, 23.49 mg of phenolic compounds, 39.46 mg of flavonoids from 1g of banana peel could be extracted (Tsai, Chou, Liu, & Hsieh, 2014) optimized ultrasound-assisted extraction of phenolic compounds from Phyllanthus emblica. Under optimal conditions (15 min of extraction time, 60°C of extraction temperature, 70% of ethanol concentration, 56 kHz of ultrasonic frequency and a 1:50 solid to solvent ratio), the leaching-out rate of phenolic compounds was up to 55.34 mg g -1 .…”
Section: Individual Compoundsmentioning
confidence: 99%